2006
DOI: 10.1182/blood-2005-09-3671
|View full text |Cite
|
Sign up to set email alerts
|

In vivo peripheral expansion of naive CD4+CD25highFoxP3+ regulatory T cells in patients with multiple myeloma

Abstract: IntroductionThe lack of clinically sufficient antitumor immune responses has been attributed to soluble inhibitory factors such as TGF␤1 1,2 or PGE 2 3-5 as well as the induction and expansion of regulatory cells. 6,7 CD4 ϩ CD25 high regulatory T cells (T reg cells) were shown to be expanded in murine tumor models. 8 Moreover, their deletion reinstated an efficient antitumor immune response leading to complete tumor regression. [9][10][11] We and others have demonstrated that CD4 ϩ CD25 high FoxP3 ϩ T reg cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
233
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(259 citation statements)
references
References 61 publications
22
233
3
1
Order By: Relevance
“…Initially, a decrease in Treg numbers was reported in MM patients, along with a defect in their ability to suppress T-cell proliferation [57]. In contrast, several more recent studies have concluded that the number of functionally intact Treg is increased in MM patients [49,50,[58][59][60]. These observations are in accordance with observations made in several other malignancies [56], and suggest that MM cells evade immune surveillance partially through the increase of suppressive Tregs [60].…”
Section: Regulatory/suppressive Cellssupporting
confidence: 79%
“…Initially, a decrease in Treg numbers was reported in MM patients, along with a defect in their ability to suppress T-cell proliferation [57]. In contrast, several more recent studies have concluded that the number of functionally intact Treg is increased in MM patients [49,50,[58][59][60]. These observations are in accordance with observations made in several other malignancies [56], and suggest that MM cells evade immune surveillance partially through the increase of suppressive Tregs [60].…”
Section: Regulatory/suppressive Cellssupporting
confidence: 79%
“…First, the lack of a specific marker for Treg has led to the assumption that only CD4ϩ,CD25 high T cells represent human Treg. (25,(38)(39)(40). However, it is unclear whether the reported reduction in the number of CD4ϩ,CD25 high Treg in SLE is compensated by an increase in the number of CD25 low ,Foxp3ϩ Treg that was not analyzed in previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…Since both Foxp3 isoforms appear to possess similar functions but their mRNA expression levels show no fixed ratio at the PBMC level, it seems important to determine total Foxp3 mRNA levels rather than quantifying the mRNA of only one of the isoforms. Fortunately, until now several studies have used PCR primer sets that amplify both Foxp3FL and Foxp3DE2 isoforms [25][26][27][28][29][30]. Nonetheless, interpretation of several other studies may be difficult since either the amplified Foxp3 region was not exactly reported [31][32][33][34] or only the full-length Foxp3 mRNA was amplified without any reasoning [35].…”
Section: Discussionmentioning
confidence: 99%